A Novel Structural and Environmental Approach: Incorporating Biohazard Litter with Hot Mix Asphalt Modifier - Sana Ullah; Asjad Javed; Usman Saif; Muhammad Adeel; Arsalan Shoukat; Uzair Amir (Spectrum of Engineering Sciences, 2025)
The quantity of plastic in solid trash is escalating owing to population growth, urbanization, and lifestyle changes, resulting in extensive littering across landscapes. Consequently, the disposal of biomedical plastic waste has emerged as a significant global issue because of its non-biodegradability. Hospitals in Pakistan generate around 250,000 tons of garbage annually. This garbage is typically incinerated in hospitals. The incineration procedure produces smoke that is highly detrimental to health. This study indicates that the accumulation of biomedical plastic waste poses significant health risks. Biomedical plastic trash includes needles, gloves, glucose containers, blood bags, and plastic trays. Various proportions of biomedical plastic waste, including Polypropylene, High-Density Polyethylene (HDPE), and Polyvinyl Chloride, were combined by weight with 80/100 pavement-grade asphalt. The Marshall Stability performance test was conducted, and its physical and volumetric features, including air spaces, voids in mineral aggregate, and voids filled with binder, were assessed in hot mix asphalt concrete (HMA). The findings indicated superior values for polymer-modified asphalt concrete. This is a sustainable procedure. The implementation of novel technologies will enhance road construction, extend road longevity, and contribute to environmental improvement. This research involves a comprehensive examination of the process for incorporating plastic debris into bituminous mixtures and conducting numerous tests. Following the literature assessment, it has been determined to use 4%, 6%, 8%, and 10% of plastic polymer (polypropylene, HDPE, and PVC) by weight of the bitumen content for our investigation. The investigation into polypropylene, HDPE, and PVC indicates that the Marshal Stability value, a strength parameter of Bituminous Concrete, has exhibited an upward trend, with maximum values rising around 16% due to the incorporation of HDPE. Additional polymers likewise exhibit a rising trend in Marshall Mix stability values. Keywords: HMA, Bitumen, Plastic waste, medical waste, biohazard material, PVC